2013
DOI: 10.1038/ncomms3022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical spin–orbital correlation in the frustrated magnet Ba3CuSb2O9

Abstract: At low temperatures, atomic magnetic moments usually exhibit some order, for example ferromagnetic order. An exception is frustrated magnets, in which the symmetry impedes the minimization of energy by pairwise magnetic interactions. In such frustrated magnets, new quantum phases, such as spin liquids, are expected. Theoretically, a quantum liquid based on the orbital degree of freedom has also been considered possible when spin and orbital degrees of freedom are entangled. However, to date, experimental obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 26 publications
(34 reference statements)
3
68
1
Order By: Relevance
“…Noncooperative static JT distortion must break threefold symmetry in each Cu 2+ site and generate anisotropic g factors within the in-plane directions in ESR experiments, similarly to the low-temperature phase of the orthorhombic sample, thus clearly inconsistent with our observations for the hexagonal sample. Significantly, orbital degree of freedom exists at high temperatures in the present samples because the orthorhombic sample undergoes a cooperative JT transition at around 200 K, and, furthermore, a dynamic orbital state has been already confirmed at 290 K in a hexagonal sample using an inelastic X-ray scattering experiment (24). Thus, our study using the single crystals without any orthorhombic components has confirmed that the hexagonal sample shows no signs of symmetry lowering on cooling and further demonstrates the absence of the noncooperative static JT distortion in all temperature regions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncooperative static JT distortion must break threefold symmetry in each Cu 2+ site and generate anisotropic g factors within the in-plane directions in ESR experiments, similarly to the low-temperature phase of the orthorhombic sample, thus clearly inconsistent with our observations for the hexagonal sample. Significantly, orbital degree of freedom exists at high temperatures in the present samples because the orthorhombic sample undergoes a cooperative JT transition at around 200 K, and, furthermore, a dynamic orbital state has been already confirmed at 290 K in a hexagonal sample using an inelastic X-ray scattering experiment (24). Thus, our study using the single crystals without any orthorhombic components has confirmed that the hexagonal sample shows no signs of symmetry lowering on cooling and further demonstrates the absence of the noncooperative static JT distortion in all temperature regions.…”
Section: Resultsmentioning
confidence: 99%
“…If the magnetic exchange interactions are enhanced to the point that they are comparable with the orbital energy, the interplay between spin and orbital would destabilize the conventional orbital-ordered state, leading to a novel spin-orbital entangled state. Indeed, such spin-orbital correlation has been already pointed out by using Huang scattering (24). According to the present structural study, the possible ground states have been already proposed theoretically, including a short-range resonating-valence bond state (25,26) and an emergent dimer state involving nearest-neighbor spin singlets with orbital order (27).…”
Section: Structural Differences Between the Hexagonal And Orthorhombicmentioning
confidence: 91%
“…Apart from the intrinsic anisotropy and the relative complexity of the orbital couplings, it has been shown that the interplay between the two frustrated degrees of freedom may lead to exotic states of matter. An x-ray scattering study of a dynamic spin-orbital state in the frustrated magnet Ba 3 CuSb 2 O 9 supports spin liquid state [28,29], while FeSc 2 S 4 [30][31][32] and the d 1 effective models on the triangular lattice [33] and on the honeycomb lattice [34,35] are found to be candidates for spin-orbital liquids in the theory. Recently remarkable progress was achieved due to rapidly developed resonant inelastic x-ray scattering (RIXS) techniques [36] which helped to explore the elementary excitations in Sr 2 CuO 3 [37,38] and Sr 2 IrO 4 [39], with antiferromagnetic (AF) and ferro-orbital (FO) order in ground states.…”
Section: Introductionmentioning
confidence: 96%
“…In this Letter, we report the THE in Ba 3 CuSb 2 O 9 (BCSO) [23][24][25][26][27][28][29], which according to us is an ideal compound to study a phonon THE owing to its strong spinlattice coupling and the presence of a spin gap. The hexagonal (6H) perovskite-type BCSO [ Fig.…”
mentioning
confidence: 99%